2014
DOI: 10.4168/aair.2014.6.6.548
|View full text |Cite
|
Sign up to set email alerts
|

Oral Lovastatin Attenuates Airway Inflammation and Mucus Secretion in Ovalbumin-Induced Murine Model of Asthma

Abstract: PurposeLovastatin is an effective inhibitor of cholesterol synthesis. A previous study demonstrated that lovastatin can also suppress airway hyperresponsiveness (AHR) in murine model of asthma. We aimed to investigate the effect of lovastatin on mucus secretion and inflammation-associated gene expression in the lungs of murine model of asthma.MethodsFemale BALB/c mice were sensitized and challenged with ovalbumin (OVA) by intraperitoneal injection, and orally administered lovastatin from days 14 to 27 post-inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 36 publications
(71 reference statements)
2
26
0
Order By: Relevance
“…The binding of activated platelets to eosinophils by P‐selectin occur in both non‐severe and severe asthma and this complex may affect the activation of eosinophil . Adhesion molecules are known to mediate migration of intravascular immune cells to surrounding tissues during inflammatory responses . In this study, we found the increased expression of VCAM and ICAM in lung tissue homogenates obtained from OVA‐sensitized and ‐challenged mice, which were not inhibited by clopidogrel treatment.…”
Section: Discussionmentioning
confidence: 61%
“…The binding of activated platelets to eosinophils by P‐selectin occur in both non‐severe and severe asthma and this complex may affect the activation of eosinophil . Adhesion molecules are known to mediate migration of intravascular immune cells to surrounding tissues during inflammatory responses . In this study, we found the increased expression of VCAM and ICAM in lung tissue homogenates obtained from OVA‐sensitized and ‐challenged mice, which were not inhibited by clopidogrel treatment.…”
Section: Discussionmentioning
confidence: 61%
“…We used human bronchial ECs instead of mouse bronchial ECs as previous literatures [2527], because previous reports showed that approximately 99 % of mouse genes have a homologue in the human genome [28], and bioinformatic analysis and human curation of 60,770 full-length mouse cDNA clones showed similarity (70–85 % identity) to known human-disease genes [29]. …”
Section: Discussionmentioning
confidence: 99%
“…(2) Attenuating airway remodelling by regulating cellular architecture and function and reducing airway epithelial changes. Studies have shown that statin treatment could reduce contractile and proliferative properties of airway smooth muscle cells during airway hyperresponsiveness [94,95], regulate MMP expressions [96,97], and decrease MUC gene expression leading to decreased mucin production and suppression of goblet cell hyperplasia [98][99][100][101][102][103][104].…”
Section: Potential Role Of Statins In the Treatment Of Respiratory DImentioning
confidence: 99%